Pelatihan Keterampilan Pengelasan Las Listrik Busur Manual Bagi Masyarakat Di Desa Bandar Bayu, Serdang Bedagai-Sumatera Utara - Pasaribu, Muhamamd Nuh Hudawi; Eswanto, Eswanto; Harahap , Muchsin (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
Skills are something that every individual must have to increase family income and open work businesses for the community. The people of Bandar Bayu Village lack skills other than farming. Because of the skills possessed by the people of Bandar Bayu Village, skills training was held in the form of manual electric arc welding skills, the aim of this training was to increase family income and open work businesses for the community. Manual electric arc welding training is given because the equipment and ferrous metal are easy to obtain and the price is affordable. Welding training for the people of Bandar Bayu Village is carried out by directly instilling ferrous metal measuring techniques, ferrous metal cutting techniques, ferrous metal joining techniques by first explaining the function of the tool, the function of ferrous metal and safety before the welding process, safety during welding and safety training after welding. arc electricity manual. The results of manual electric arc welding skills training for the people of Bandar Bayu Village are that the people are able to weld iron materials and produce two tables and two stoves.